Pengaruh Harga, Promosi, dan Citra Merek terhadap Keputusan Pembelian Sepeda Motor Honda di Kabupaten Purworejo - Shinta Febriana; Anna Probowati; Dewi Shanti Nugrahani (Progress, 2026)
The study aims to determine whether partially and simultaneously there is a positive and significant influence of the independent variables—price, promotion, and brand image—on the dependent variable, which is the purchase decision. The population in this research consists of Honda motorcycle consumers in Purworejo Regency. The sampling method used is purposive sampling, with a total sample size of 100 respondents. Data collection was conducted using questionnaires with alternative answer choices based on a Likert scale consisting of 5 options. The questionnaires were pre-tested and fulfilled the requirements for validity and reliability.The data were analyzed using multiple linear regression analysis through t-tests and F-tests. The independent variables are price, promotion, and brand image, while the dependent variable is the purchase decision. The results of the study show that, partially, price has a positive and significant influence on purchase decisions; promotion has a positive and significant influence on purchase decisions; and brand image has a positive and significant influence on purchase decisions. Simultaneously, price, promotion, and brand image collectively have a positive and significant influence on purchase decisions.